Improving Production Line Performance: A case study - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba; Abdul Ghani, Jaharah (2010)
A case-based research method was chosen with the aim to provide an exemplar of practice and test the proposition that the use of simulation can improve productivity. Three alternatives were performed by considering the aspects of operator, machine, and workstation to define productivity improvement alternatives for operation optimisation. The research determines the optimum result to improve the current operation system. The experiments on simulated and real data clearly indicate that the productivity improvement in the current performance can be achieved by re-allocating the number of operators and machines effectively instead of a combination. The paper presents a novel example of the use of simulation to estimate the production line performance. The paper highlights this method by addressing this operational issue and the likelihood of the success of the strategic decision to improve productivity.